Sex-related disparities in aortic stenosis from disease awareness to treatment: a state-of-the-art review - Appleby, Clare; Bleiziffer, Sabine; Bramlage, Peter; Delgado, Victoria; Eltchaninoff, Helene; Gebhard, Catherine; Hengstenberg, Christian; Kurucova, Jana; Marx, Philipp; Rudolph, Tanja K; Wojakowski, Wojtek (Journal of thoracic disease, 2024)
This state-of-the-art review aimed to synthesize evidence from various sex-stratified studies on aortic stenosis (AS), focusing on the difference in clinical presentation, anatomical characteristics, pathophysiology, and management of AS. In comparison to men, women with AS are present at later stages, are older, more symptomatic, frailer, and exhibit higher operative risk [Society of Thoracic Surgeons (STS) score]. Women tend to have smaller aortic valve (AV) areas and left ventricular (LV) outflow tract, leading to lower stroke volumes (SVs) than men and have a higher prevalence of paradoxical, low-flow, low-gradient AS. In women, chronic pressure overload due to AS results in concentric LV remodelling and hypertrophy, characterized by reduced LV cavities, higher filling pressures, lower wall stress, and more diastolic dysfunction. Conversely, men exhibit more dilated eccentric LV remodelling and hypertrophy. AVs in women are less calcified but more fibrotic. Moreover, women are often underdiagnosed, have severity underestimated, and experience delays or receive fewer referrals for AV replacement (AVR). However, women tend to benefit from transcatheter AVR (TAVR) with a long-term survival advantage over men, although the incidence of vascular complications and bleeding events in 30 days after TAVR is higher in women. Surgical AVR (SAVR) in women has high operative risk, is technically demanding and has poorer outcomes with increased mortality at 30 days compared to men. According to the STS score and EuroSCORE, the female sex itself is considered a risk factor for SAVR. Therefore, addressing sex-related disparities in AS and increasing awareness among physicians promises improved diagnosis and treatment, facilitating equitable care and the development of sex-specific personalized medicine.